Heavy metal toxicity-implications on metabolism and health - JHUMI JAIN,; PAMMI GAUBA, (International Journal of Pharma and Bio Sciences, 2017)
Heavy metal toxicity leads to major threats to the environment, causing adverse effects on the living beings. Since ages, heavy metals are been used by the humans. The threatening health disorders of heavy metals are known, but still exposure continues. The increased global population, industrialization and urbanization are some of the major reasons for the contamination. The release of heavy metals occurs from various anthropogenic activities, agronomic practices and dumping of various types of wastes. Heavy metals such as arsenic (As), cadmium (Cd), lead (Pb) and mercury (Hg) are the most toxic heavy metals, according to WHO ranking of the top ten potential chemicals of major public health concern. They alter the food chain by disturbing the biochemical apparatus of the living organisms, leading to life threatening disorders. This paper reviews the impact on the metabolism occurred by the exposure to these top four harmful heavy metals for public health concern.